Infections in early life and premature acute coronary syndrome: A case-control study. (October 2016) - Qanitha, Andriany; de Mol, Bastianus AJM; Pabittei, Dara R; Mappangara, Idar; van der Graaf, Yolanda; Dalmeijer, Geertje W; Burgner, David P; Uiterwaal, Cuno SPM
Background: Infections in young children may affect the vasculature and initiate early atherosclerosis. Whether infections experienced in childhood play a part in adult clinical cardiovascular disease remains unclear. We investigated the association between infections in early life and the occurrence of premature coronary heart disease. Methods: We conducted a population-based case-control study of 153 patients with a first acute coronary syndrome before the age of 56 years and 153 age- and sex-matched controls. Any history of severe infections in childhood and adolescence was obtained, together with clinical and laboratory measurements and other cardiovascular risk factors. We developed an infection score for the overall burden of early life infections. Conditional logistic regression was used to assess the associations. Results: Infections experienced in early life increased the risk of acquiring acute coronary syndrome at a young age with an odds ratio (OR) of 2.67 (95% confidence interval (CI) 1.47–4.83, p  = 0.001). After adjustments for traditional risk factors, lifestyle, dietary patterns, socio-economic status and parental history of cardiovascular events, these associations remained significant and changed only slightly. There was an indication for an interaction between infections in early life and current cardiovascular risk (Framingham Risk Score (FRS); p -interaction = 0.052). Within participants with a low FRS (<10%), the OR of early life infection for acute coronary syndrome was 1.49 (95% CI 0.72–3.08, p  = 0.283); within participants with an intermediate FRS (10–20%), the OR was 4.35 (95% CI 1.60–11.84, p  = 0.004); and within participants with a high FRS (>20%), the OR 10.00 (95% CI 1.21–82.51, p  = 0.032). Conclusion: Infections in early life may partly explain premature coronary heart disease in adulthood and may potentiate traditional cardiovascular risk factor effects.